Peran Guru Pendidikan Agama Islam (PAI) Dalam Pengembangan Metode Dan Evaluasi PAI : Studi Komparatif di Sekolah Dasar Negeri 1 Talok dan Sekolah Dasar Negeri 3 Senggreng - Ummi Ulfatus Syahriyah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2023)
This article aims to describe the role of Islamic Education teachers in developing methods and evaluation of PAI learning. Educators have a very vital position in the learning process. The level of success in achieving learning materials can be measured by the quality of the educators. The condition of PAI in elementary schools is currently facing various challenges. While the teacher is required to realize the role and noble task. Considering that the goal of Islamic education does not only stop at the physical-material level, but also spiritual-spiritual and mental-emotional. The research method used in this research is a qualitative approach with a comparative study conducted at SD Negeri 1 Talok and SD Negeri 3 Senggreng. Data collection techniques using observation, interviews, and documentation. The results showed that the role of the PAI teacher in developing the method and evaluation of PAI learning at SD Negeri 1 Talok and SD Negeri 3 Senggreng was as a facilitator, mentor, role model, and evaluator